EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) PADA SISWA SMP - Rezki Ramdani (Jurnal Penalaran dan Riset Matematika, 2022)
This study aims to determine the effectiveness of learning mathematics through the application of the Numbered Head Together (NHT) cooperative model in class IX-G students of SMP Negeri 21 Makassar. Criteria for the effectiveness of learning can be seen from the increased student learning outcomes and classical learning mastery, at least 75%, the average percentage of student activity in learning mathematics and students who give a positive response to learning mathematics reaches 75%. This type of research is pre-experimental involving one class as the experimental class. The experimental class that became the sample in this study was selected using the Cluster Random Sampling technique. The research design used was the One Group Pretest-Posttest Design. This research was conducted for 6 (six) meetings. The data collection technique used was a mathematics learning achievement test to measure student learning outcomes before and after learning mathematics through the application of the Numbered Head Together (NHT) cooperative model, student activity observation sheets to see student activity during the learning process, and student response questionnaires to knowing students' responses to the implementation of learning mathematics by using the cooperative learning model of the Numbered Head Together (NHT) type. The results of this study indicate that, 1) The results of students' mathematics learning after the application of the Numbered Head Together (NHT) cooperative learning model are categorized as "Increasing" and "Completed" classically, 2) Student activities in learning mathematics are categorized as "Active", and 3) Student responses to learning mathematics are categorized as "positive". Based on the results of this study, students have met the criteria for the effectiveness of learning mathematics, so it can be concluded that learning mathematics is effectively implemented through the application of the Numbered Head Together (NHT) cooperative model in class IX-G students of SMP Negeri 21 Makassar.